(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
It is possible to involve students in learning process more actively using the new information technologies, research method and co-operation. The paper contains theoretical base of student research work as a component o f studying process in higher education establishments using IT. The research investigates student personality development and interconnection with productivity of studying process. The author analyses researches on productive interaction in the context of computer-supported collaborative learning in science, computers in the community of classrooms, a sociocultural perspective on the human-technology link and computer-mediated communication. The paper contains empirical research results about productivity of studying process on an experimental base increasing a part of the research work and problem solving using IT and collaboration in studying process of Computer science course in Vidzeme University College.